A linguistic analysis of effective speeches - Othman, Khairiah; Ismail, Anis Izzati (American Scientific Publishers, 2018)
Recent decades have witnessed the usage of the English language as an effective medium for various communicative functions including disseminating information and conveying messages. This study explored linguistic devices that have contributed towards effective speeches of a prominent speaker, Dr. Zakir Naik. Content analysis on three speeches by Dr. Zakir Naik was employed. This study investigated sentences or phrases in Dr. Zakir Naik’s speeches containing linguistic features. Findings indicate that Dr. Zakir Naik mainly employed linguistic features namely rhetorical question to gain support from his audience, repetition to emphasize important information, stir audience’s emotion and make message more memorable while Islamic English to maintain the Arabic terms in the English language due to the absence of equivalent English words. The findings of this exploratory study provide essential theoretical implications for future speakers to deliver effective speeches.